Hybrid nanostructures based on g-C3N4 for photocatalytic hydrogen generation - Chan, Pei Boon (2015)
With the increasing concern of energy shortage and severe environmental issues, large scale production of hydrogen by photocatalytic water splitting using a semiconductor photocatalyst has been developed. The good photocatalytic performance of g-C3N4 due to its unique electronic band structure, high thermal and chemical stability make it as a promising candidate for semiconductor photocatalyst in photocatalytic hydrogen evolution. However, the fast recombination rate of electron-hole pairs restricts its application as photocatalyst. Coupling of noble-metal-free co-catalyst, Ni(dmgH)2 with g-C3N4 allows a steady and efficient photocatalytic hydrogen generation. This study aim to further enhance the photocatalytic activity of g-C3N4/Ni(dmgH)2 by reducing the size of Ni(dmgH)2 nanowires. Samples of g-C3N4/Ni(dmgH)2 with different concentration EDTA are prepared. The size of the Ni(dmgH)2 are investigated under SEM microscope and their photocatalytic H2 evolutions were carried out in the presence of TEOA solution as sacrificial reagent. Result showing that EDTA has the capability to slow down the grow of Ni(dmgH)2 with the formation of Ni(EDTA) complex and reduce the size of Ni(dmgH)2 nanowires. g-C3N4/Ni(dmgH)2 with 1.5 EDTA exhibit the highest hydrogen production rate of 40.37µmolg-1h-1 which is 2.52 times higher than the H2 production rate of g-C3N4/Ni(dmgH)2 without EDTA. This study demonstrates the adding of EDTA could reduce the size of Ni(dmgH)2 which in turn enhance the photocatalytic hydrogen evolution of g-C3N4/Ni(dmgH)2.